Learning-dependent structural plasticity of intracortical and sensory connections to functional domains of the olfactory tubercle - Sha, Md Fazley Rabbi; Koga, Yuriko; Murata, Yoshihiro; Taniguchi, Mutsuo; Yamaguchi, Masahiro (Frontiers in Neuroscience, 2023)
The olfactory tubercle (OT), which is a component of the olfactory cortex and ventral striatum, has functional domains that play a role in odor-guided motivated behaviors. Learning odor-guided attractive and aversive behavior activates the anteromedial (am) and lateral (l) domains of the OT, respectively. However, the mechanism driving learning-dependent activation of specific OT domains remains unknown. We hypothesized that the neuronal connectivity of OT domains is plastically altered through olfactory experience. To examine the plastic potential of synaptic connections to OT domains, we optogenetically stimulated intracortical inputs from the piriform cortex or sensory inputs from the olfactory bulb to the OT in mice in association with a food reward for attractive learning and electrical foot shock for aversive learning. For both intracortical and sensory connections, axon boutons that terminated in the OT domains were larger in the amOT than in the lOT for mice exhibiting attractive learning and larger in the lOT than in the amOT for mice exhibiting aversive learning. These results indicate that both intracortical and sensory connections to the OT domains have learning-dependent plastic potential, suggesting that this plasticity underlies learning-dependent activation of specific OT domains and the acquisition of appropriate motivated behaviors.